2017
DOI: 10.1111/bph.14049
|View full text |Cite
|
Sign up to set email alerts
|

Different protein kinase C isoenzymes mediate inhibition of cardiac rapidly activating delayed rectifier K+ current by different G‐protein coupled receptors

Abstract: Our results indicated that inhibition of I by activation of α -adrenoreceptors or AT receptors were mediated by PKCα and PKCε isoforms respectively, through different molecular mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 41 publications
6
14
0
Order By: Relevance
“…4, A and B). This observation is consistent with previous literature investigating acute PKC activation (Thomas et al, 2003;Cockerill et al, 2007;Wang et al, 2008Wang et al, , 2009Liu et al, 2017). Our results further demonstrated that PKC-mediated I hERG inhibition is slowly reversible.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…4, A and B). This observation is consistent with previous literature investigating acute PKC activation (Thomas et al, 2003;Cockerill et al, 2007;Wang et al, 2008Wang et al, , 2009Liu et al, 2017). Our results further demonstrated that PKC-mediated I hERG inhibition is slowly reversible.…”
Section: Discussionsupporting
confidence: 94%
“…We investigated the molecular mechanisms underlying PMA-mediated I hERG reduction. Previous studies have suggested that the N terminus of hERG is required for PKC-mediated I hERG reduction (Cockerill et al, 2007;Liu et al, 2017). We obtained novel evidence that the N terminus is involved in PMA-mediated I hERG reduction.…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…Goe 6983 (10 −6 mol·L −1 at the serosal side; Table 2), another broad spectrum inhibitor of PKCs (Liu, Wang, Zhang, Shen, & Xu, 2017).…”
Section: Missing Evidence For Ionotropic Function Of Nicotinic Recementioning
confidence: 99%